Adapting as Pioneers: A Phenomenological Study of First-Batch Medical Students in a New Medical Faculty - Ifitahurroza, Hilma Tsurayya; Andyastanti, Tisnalia Merdya; Weningtyas, Anditri; Wibowo, Rosalie Aurellie; Yusangka, Callysta Neysa (Jurnal Kajian Bimbingan dan Konseling, 2026)
Entering medical faculty is inherently demanding for first year student and the challenges are amplified for first-batch students in newly established faculties. These students must navigate academic, social, and professional adaptation simultaneously with evolving institution systems. Understanding their adaptation is essential to support success and resilience. This study aimed to explore the adaptation experiences of first-batch medical students in their first year in a new medical faculty. A descriptive phenomenological approach was employed. Data were collected through semi-structured interviews conducted in September 2024 with seven first-year students at the Faculty of Medicine, State University of Malang, established in 2023. Participants were selected using purposive sampling to ensure variation in characteristics and to achieve data saturation. Data were transcribed verbatim and analyzed using thematic analysis. Lecturer perspectives were also included to enhance triangulation. Thematic analysis showed five main themes: (1) student motivation, (2) perceived benefits, (3) challenges, and (4) adaptation strategies in the first year of medical education. These findings highlight that students experience a dual dynamic of vulnerability and opportunity during their transition. Their high motivation and close interaction with faculty provide opportunities for growth, resilience, and professional identity formation. Ensuring structured support and continuous faculty development is crucial for sustaining their success.